Participatory Leadership by School Principals in Enhancing the Quality of Education - Arip Hertanto; Syunu Trihantoyo; Amrozi Khamidi (Universitas Teuku Umar, 2025)
This analysis synthesizes scholarly literature to explore the significant link between participatory leadership enacted by school principals and the enhancement of educational quality. Participatory leadership, characterized by the distribution of control in decision-making, emerges as a unifying framework for fostering positive change within schools. The analysis reveals that this leadership style cultivates a supportive, collaborative, and inclusive environment, valuing the contributions of all stakeholders. Key dimensions of enhanced educational quality include teacher empowerment and effectiveness, the development of trust-based school climates, the promotion of innovation and adaptability, and the improvement of student engagement and achievement. By actively involving teachers, staff, and students in decision-making processes, participatory leadership creates a positive feedback loop that benefits the entire school community and aligns with established leadership theories emphasizing empowerment and collective intelligence. While challenges to implementation exist, the literature underscores the potential of participatory leadership to drive meaningful improvements in education.